1987
DOI: 10.1111/j.1525-1470.1987.tb00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Hair Growth in Children

Abstract: Abnormalities in the hair growth of children are common reasons for referral to a dermatologist or pediatrician. There is wide variation in the normal sequence of development of hair form and pattern in childhood and adolescence. Very occasionally, abnormalities may be a component of complex metabolic disorders. Therefore it is important to recognize the normal growth of children's hair. Most diagnoses of hair disorders may be made on clinical examination and inspection of hair shafts and roots under a light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 67 publications
1
46
0
Order By: Relevance
“…However, no clear difference was visible between the age of 5 and 8 years. HCC may be further elevated during the first years of life when hair morphology and growth is subject to major changes [17]. After the age of 2, hair has been observed to increase in cross-sectional surface area and in the percentage of medullated hair with age up to puberty [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear difference was visible between the age of 5 and 8 years. HCC may be further elevated during the first years of life when hair morphology and growth is subject to major changes [17]. After the age of 2, hair has been observed to increase in cross-sectional surface area and in the percentage of medullated hair with age up to puberty [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although the established use of stable isotopes in archaeology as diet and locational indicators frequently uses bone collagen or tooth enamel, bone is constantly remodeled throughout life, presenting an averaged dietary measurement, whereas tooth enamel represents the childhood signature. In contrast, scalp hair grows 1 cm a month on average in most human populations and, once formed, does not undergo further biogenic alteration (24).…”
mentioning
confidence: 99%
“…It has been proposed that racial differences are implicated in the occurrence of this entity, Mediterranean women being more subjected to abnormal hair growth [24]while Mongoloid women present a relative absence of body hair [25]. As the girls in the control group, most of the patients were of Mediterranean descent while a few were natives.…”
Section: Discussionmentioning
confidence: 99%
“…Barth [25]studied a group of 6 children (2 boys and 4 girls) with hypertrichosis and concluded that he did not know if the pattern of hypertrichosis of these children represented as abnormal entity or if it occurred as an extreme form of normal hair growth. In order to distinguish between hypertrichosis and normal hair growth, we have evaluated our patients through a careful clinical assessment and compared them with a group of normal girls who did not complain about excessive growth of their body hair.…”
Section: Discussionmentioning
confidence: 99%